Hyperoxic Vasoconstriction of Human Pulmonary Arteries: A Novel Insight into Acute Ventricular Septal Defects - Ariyaratnam, Priyadharshanan (Hindawi Publishing Corporation, 2013)
Objectives. Acute rises in pulmonary artery pressures following postinfarction ventricular septal defects present a challenge. We hypothesised that the abnormally high oxygen content exposure to the pulmonary arteries may be a factor. We investigated the contractile responses of human pulmonary arteries to changes in oxygen tension. Methods. Isometric tension was measured in large and medium sized pulmonary artery rings obtained from lung resections for patients with bronchial carcinoma (n = 30). Fresh rings were mounted in organ baths bubbled under basal conditions with hyperoxic or normoxic gas mixes and the gas tensions varied during the experiment. We studied whether voltage-gated calcium channels and nitric oxide signalling had any role in responses to oxygen changes. Results. Hypoxia caused a net mean relaxation of 18.1% ± 15.5 (P < 0.005) from hyperoxia. Subsequent hyperoxia caused a contraction of 19.2% ± 13.5 (P < 0.005). Arteries maintained in normoxia responded to hyperoxia with a mean constriction of 14.8% ± 3.9 (P < 0.005). Nifedipine inhibited the vasoconstrictive response (P < 0.05) whilst L-NAME had no effect on any hypoxic vasodilatory response. Conclusions. We demonstrate that hyperoxia leads to vasoconstriction in human pulmonary arteries. The mechanism appears to be dependent on voltage-gated calcium channels. Hyperoxic vasoconstriction may contribute to acute rises in pulmonary artery pressures.